PENGEMBANGAN MODEL PEMBINAAN DISIPLIN PESERTA DIDIK DALAM MEMBANGUN KARAKTER BANGSA BERBASIS KELAS DI SMA NEGERI SUMATERA BARAT - Fitria Kasih; Helma Helma (Ta'dib, 2012)
The aims of the first year research were to figure out 1) forms and level of students’ discipline, 2) factors influencing students’ discipline, 3) forms of discipline encouragement carried out by the teachers. The result of the research will be used as a foundation for developing a model for students’ discipline management in order to build classroom-based nation character in West Sumatera senior high schools in the second year. The first research method employed in the first year was descriptive analysis while in the second one was applied research and mixing research method. To collect the data, questionnaire was administered to the students and in-depth interview was for the teachers. The population was students from three regencies and municipalities: Kabupaten Agam, Kota Payakumbuh and Kabupaten Tanah Datar where two school from each of the regions were chosen randomly. Sampling techniques employed was area purposive sampling. The data for the first year was analyzed by means of percentage formula while for the second year was t-test. The ending product of the research was a model. The findings of the research showed that forms and level of students discipline were good. Next, factors influencing students’ discipline were various. Last, forms of discipline encouragement carried out by the teachers were quite good. It was recommended from the first year research that a model for students’ discipline management in order to build classroom-based nation character in West Sumatera senior high schools was really needed.Kata kunci: pembinaan, disiplin, karakter bangsa, kelas